Is red blood cell distribution width a prognostic factor for colorectal cancer? A meta-analysis - Wen, Ze-Lin; Zhou, Xiong; Xiao, Da-Chun (Frontiers in Surgery, 2022)
Background RDW might be an easy and cost-effective pre-operative prognostic factor for cancer patients. The aim of the current study was to analyze whether red blood cell distribution width (RDW) was a prognostic factor for colorectal cancer (CRC) patients who underwent radical surgery. Methods We conducted the searching strategy in three databases including the PubMed, Embase and Cochrane Library from the inception to May 07, 2022, to find eligible studies. In this meta-analysis, we focused on the prognosis. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated for overall survival (OS), disease-free survival (DFS) and cancer-specific survival (CSS). Results A total of seven studies involving 7,541 patients were included in this meta-analysis. After pooling up the HRs, red blood cell distribution width-coefficient of variation (RDW-CV) was not an independent prognostic factor of OS (HR = 1.48, I2 = 90%, 95% CI = 0.93 to 2.36, P = 0.10), however, red blood cell distribution width-standard deviation (RDW-SD) was an independent prognostic factor of OS (HR = 1.99, I2 = 0%, 95% CI = 1.59 to 2.49, P < 0.01). As for DFS, we found that RDW-CV (HR = 1.51, I2 = 83%, 95% CI = 0.94 to 2.43, P = 0.09 < 0.10) and RDW-SD (HR = 1.77, I2 = 56%, 95% CI = 0.91 to 3.43, P = 0.09 < 0.10) were both the independent prognostic factors. In terms of CSS, we found that RDW-CV was not an independent prognostic factor (HR = 1.23, I2 = 95%, 95% CI = 0.72 to 2.10, P = 0.46). Conclusion RDW-SD was an independent prognostic factor of OS and DFS, and RDW-CV was an independent prognostic factor of DFS.